Development of e-governance as a tool for increasing transparency and accountability of government in Ukraine - Ninyuk, Inna I. (My University, 2025)
The study assessed the development of e-governance tools in enhancing transparency and accountability within the government of Ukraine. Ukraine’s efforts to combat corruption have become particularly notable, especially by reinforcing anti-corruption frameworks. Successful investigations, enforcement measures, and resulting convictions reflect the government’s firm commitment to addressing corruption. Despite these measures, Ukraine was ranked 105th out of 180 countries in the 2024 Corruption Perceptions Index. The study’s main objective was to evaluate the development of such tools and their impact on governance outcomes. A secondary research approach was employed, relying on existing data sources and utilising content analysis as the primary analytical method. The findings indicate, among other things, that platforms such as Diia and Prozorro have significantly contributed to enhanced accountability, efficiency, costeffectiveness, and transparency in governmental operations. kraine has increased public trust in state institutions. through digitalising public services processes.
Keywords: corruption; e-procurement; framework; public trust; digitisation; service delivery